EFFECT OF THE VISION OCLUSION ON DYNAMIC BALLANCE ON UNSTABLE PLATAFORM (Fiep Bulletin - online, 2012)
The present study analyzed the effect of the visual occlusion on balance on an unstable platform. Fourteen young adults participated on the study aging between 19 and 28 years old. The task consisted on the maintenance of the balance on an unstable platform during ten seconds. The experiment was performed under conditions with and without vision. The t Student test for dependent samples showed lower balance time (P
Keywords: Postural control; sensorial information; instability.